Peakvue Method Implementation with Microcontroller ATMEGA32 - SOMALI (NIM 13103010), YUDHI
Bearing, as rotation equipment support, is a common component which is used in industrial equipment. Bearing may have some defects due to excessive load during its operation. This local defect may cause vibration with unique characteristics. Bearing defect in early stages can be detected with vibration peak value calculation method (peakvue) which is provided in CSI 2120 analyzers. The same method can also be implemented in microcontroller, since CSI 2120 uses microcontrollers to do the same analysis. This research is done with the implementation of peakvuemethod which is based on MATLAB software. Then the same implementation is used based on microcontroller ATMEGA32 to detect some bearing local defects. Later, each of them is implemented in three specimens bearing FAG 6211. The result of two types implementations is expected so that the use of CSI 2120 may no longer need in peakvue calculation. The research, both in MATLAB and microcontroller, results in some peak values which is similar with CSI 2120 peak value calculation, while some values are different. Some difference value may due to slight difference in signal conditioning between this two methods and invalidated results with CSI 2120 peakvue analysis.